Tick salivary gland extract and interleukin-2 stimulation enhance susceptibility of lymphocytes to infection by Theileria parva sporozoites - Shaw, M.K.; Tilney, L.G.; McKeever, Declan J. (American Society for Microbiology, 1993)
Intracellular parasites show host cell specificity, and precise information on the range of host cells is a prerequisite for the identification of host molecules that account for the specificity and are involved in entry processes. The sporozoite stage of the tick-borne protozoan parasite Theileria parva binds to and enters bovine lymphocytes, but precise information on the susceptibility of other cell types present at the tick attachment site is unavailable. We quantitatively examined the susceptibility of cell types known to be present at the tick attachment site by a previously established in vitro assay. Apart from lymphocytes, sporozoites also bind to and enter macrophages and afferent lymph veiled cells; they do not bind to or enter fibroblasts, granulocytes, or erythrocytes. Sporozoites are not phagocytosed by the macrophages or veiled cells but enter them as they do lymphocytes. Since the tick attachment site is a region of cellular inflammation, we also examined the effects of agents known to be present in this area on lymphocyte susceptibility. Short-term preincubation of lymphocytes with tick salivary gland extract, with compounds that induce lymphocyte proliferation, or with interleukin-2 (IL-2), a cytokine produced by activated lymphocytes, increased host cell susceptibility by between 30 and 60%. The IL-2-induced increase in host cell susceptibility could be prevented by treating the lymphocytes with the monoclonal antibody IL-A 111, which reacts with the bovine IL-2 receptor alpha chain and inhibits IL-2-driven cell proliferation. The changes induced by tick salivary gland extract and IL-2 occurred in less than 90 min. Similarly, peripheral blood mononuclear cells from an animal previously immunized with a nonrelated antigen (trypanosome variant surface glycoprotein) and stimulated in vitro with the same antigen showed increases in host cell susceptibility of between 70 and 125%. In contrast, treatment of lymphocytes with gamma interferon did not induce any increase in host cell susceptibility.